Twenty‐year longitudinal birth cohort study of individuals diagnosed with autism spectrum disorder before seven years of age. (11th April 2022) - Iwasa, Mitsuaki; Shimizu, Yasuo; Sasayama, Daimei; Imai, Miho; Ohzono, Hiroko; Ueda, Miori; Hara, Ikuko; Honda, Hideo
Abstract : Background: Previous longitudinal studies have demonstrated that psychosocial outcomes for autistic adults are very limited. However, most studies are clinic‐based and liable to selection bias and major methodological problems. Methods: We conducted a long‐term follow‐up study with 278 autistic individuals from our previous birth cohort study comprising 31, 426 individuals. All participants were born in northern Yokohama between 1988 and 1996, diagnosed with autism spectrum disorder (ASD) by age seven, and followed up over 20 years. A total of 170 consented to participate in the study. Outcome measures included overall social functioning based on work, independent living, and friendships. Moreover, the time‐use data concerning social participation and activities of daily living were compared with the general population. Results: Psychosocial outcomes in adulthood (average age 25) were very good in 13.7%, good in 25.0%, fair in 31.0%, poor in 25.6%, and very poor in 4.8% of the participants. The majority participated in major life areas of and work and education (96.4%), sports (82.1%), and recreational activities and/or hobbies (98.8%). The proportion of participants who engaged in housework and self‐care was comparable to that of the general population. Participants with IQ < 50 at age five had significantly worse outcomes than those with higher IQ; however, for those with IQ ≥ 50, outcomes were not significantly associated with IQ levels. Conclusions: Although complete independence was difficult to accomplish, many autistic adults engaged in organized community activities and housework and self‐care. Time‐use survey could offer a variety of data in investigating psychosocial outcomes of ASD cross‐culturally.